Lieux ludiques: « Les Prisonniers » de Maupassant - Färnlöf, Hans (Romanica Silesiana, 2021)
This study examines the role of topoi in the short story “Les Prisonniers” (The Prisoners) by Maupassant. For historical reasons, the notion of topos is preferred to that of the stereotype, as the latter indicates a manner of conceiving reality from a 20th century perspective (and thus posterior to Maupassant’s authorship). The analysis of the topoi shows that the author brings to play intertextual references linked to the tradition of the folktale and the short story. In foregrounding the story, Maupassant prepares two opposing scenarios. Following the transgressive plot, the initially dominant features of the story are overthrown. The functionality of the narrative elements, entering as units in an elaborated plot, leads to a view of the story primarily as a fictional construction playing with topoi, rather than as an expression of Maupassant’s stereotyped vision of reality.